2018
DOI: 10.3389/fpls.2018.01297
|View full text |Cite|
|
Sign up to set email alerts
|

The Tryptophan decarboxylase 1 Gene From Aegilops variabilis No.1 Regulate the Resistance Against Cereal Cyst Nematode by Altering the Downstream Secondary Metabolite Contents Rather Than Auxin Synthesis

Abstract: Cereal cyst nematode (CCN, Heterodera avenae) is a most important pathogen of wheat and causes tremendous yield loss annually over the world. Since the lack of resistance materials among wheat cultivars, identification and characterization of the resistance-related genes from the relatives of wheat is a necessary and efficient way. As a close relative of wheat with high resistance against CCN, Aegilops variabilis No.1 is believed to be a valuable source for wheat breeding against this devastating disease. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
(94 reference statements)
1
16
0
Order By: Relevance
“…In this research, we selected three wheat genotypes, including wild emmer, durum, and bread wheat, to address the fundamental question of the effect of domestication on plant resistance against aphids. To understand the overall gene levels and the differential gene expression between genotypes [75], we compared the transcriptomes of 11-day-old seedlings of the three genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, we selected three wheat genotypes, including wild emmer, durum, and bread wheat, to address the fundamental question of the effect of domestication on plant resistance against aphids. To understand the overall gene levels and the differential gene expression between genotypes [75], we compared the transcriptomes of 11-day-old seedlings of the three genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…High throughput methods like RNA-seq analysis are widely used to identify the 466 differential expression of genes (Huang et al, 2018). Hence, RNA-seq was performed to find the 467 differential expression of genes in S. viridis leaves following 96 h of herbivore feeding.…”
Section: Discussion 446mentioning
confidence: 99%
“…Nevertheless, the effects 487 of serotonin on herbivore growth and feeding behavior is not yet clear. For example, previous 488 experiments using mutants of CYP71A1, which encodes to T5H enzyme, showed that lack of 489 serotonin increased resistance to planthopper (Nilaparvata lugens) (Lu et al, 2018), while 490 exposure to the striped stem borer (Chilo suppressalis) induced serotonin synthesis in wild type 491 rice plants (Ishihara et al, 2008a). This suggests that the function of serotonin in defense is 492 species-specific.…”
Section: Discussion 446mentioning
confidence: 99%
See 1 more Smart Citation
“…A gene encoding tryptophan decarboxylase1 was strongly induced in Ae. variabilis roots during early stages of nematode infection compared to non-infected controls, but when silenced using the barley striped mosaic virus gene silencing system, the plant roots showed enhanced susceptibility to infection [72]. Tryptophan decarboxylase converts tryptophan to tryptamine, a precursor for the synthesis of secondary metabolites and the phytohormone IAA.…”
Section: Genes Associated With Disease Resistance Against Soilborne Pmentioning
confidence: 99%